2009
DOI: 10.3758/cabn.9.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Activation of right parietal cortex during memory retrieval of nonlinguistic auditory stimuli

Abstract: In neuroimaging studies, the left ventral posterior parietal cortex (PPC) is particularly active during memory retrieval. However, most studies have used verbal or verbalizable stimuli. We investigated neural activations associated with the retrieval of short, agrammatical music stimuli (Blackwood, 2004), which have been largely associated with right hemisphere processing. At study, participants listened to music stimuli and rated them on pleasantness. At test, participants made old/new recognition judgments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 19 publications
8
36
1
Order By: Relevance
“…A corollary of this principle is that episodic features that are encoded primarily by one cerebral hemisphere should be linked by vPPC bindings in that same hemisphere. This prediction is supported by the findings of Klostermann et al (2009), in which retrieval-related activity in the right vPPC was found for stimuli (unfamiliar music clips) known to be processed in the right hemisphere. On this view, the frequently observed finding of left-lateralized vPPC activity (for words, pictures, and faces) is attributed to vPPC bindings of verbal or semantically based features known to be represented primarily in the left hemisphere.…”
Section: Implications Of Cobra Theorysupporting
confidence: 68%
See 2 more Smart Citations
“…A corollary of this principle is that episodic features that are encoded primarily by one cerebral hemisphere should be linked by vPPC bindings in that same hemisphere. This prediction is supported by the findings of Klostermann et al (2009), in which retrieval-related activity in the right vPPC was found for stimuli (unfamiliar music clips) known to be processed in the right hemisphere. On this view, the frequently observed finding of left-lateralized vPPC activity (for words, pictures, and faces) is attributed to vPPC bindings of verbal or semantically based features known to be represented primarily in the left hemisphere.…”
Section: Implications Of Cobra Theorysupporting
confidence: 68%
“…The successful retrieval effect has been observed using a variety of stimuli types, such as visual and spoken words, pictures, faces, natural sounds, and music clips (Cansino, Maquet, Dolan, & Rugg, 2002;Dobbins & Wagner, 2005;Guerin & Miller, 2009;Henson, Rugg, Shallice, Josephs, & Dolan, 1999;Klostermann, Kane & Shimamura 2008;Klostermann, Loui, & Shimamura, 2009;Leube, Erb, Grodd, Bartels, & Kircher, 2003;Shannon & Buckner, 2004;Svoboda, McKinnon, & Levine, 2006). It has also been observed under various test conditions and manipulations, such as recognition memory, cued recall, source memory, confidence judgments, and motor responses (see de Zubicaray et al, 2007;Shannon & Buckner, 2004;Vilberg & Rugg 2008;Wagner et al, 2005).…”
Section: Parietal Contributions To Episodic Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…One critical finding is that vPPC activity is tied to brain regions that encode event features. For example, Klostermann et al (2009) found only right vPPC activity during retrieval of non-Western music that is processed primarily by the right hemisphere. In other studies, left-lateralized vPPC activity is observed, which suggests that verbal or semantic processes are typically implemented during retrieval.…”
Section: Episodic Retrieval As a Whole Brain Phenomenonmentioning
confidence: 99%
“…For instance, successful retrieval effects occur when the encoded stimuli are words (Donaldson, Petersen, & Buckner, 2001;Henson, Hornberger, & Rugg, 2005;Herron, Henson, & Rugg, 2004;Kahn et al, 2004), faces (Guerin & Miller, 2009;Leube, Erb, Grodd, Bartels, & Kircher, 2003), pictures (Cansino, Maquet, Dolan, & Rugg, 2002;Dobbins & Wagner, 2005;Shannon & Buckner, 2004;Slotnick, Moo, Segal, & Hart Jr., 2003;Weis, Klaver, Reul, Elger, & Fernández, 2004), natural sounds (Shannon & Buckner, 2004), and non-verbal musical stimuli (Klostermann, Loui, & Shimamura, 2009). Effects also occur across different response contingencies -when subjects are instructed to respond to both old and new items, old items only, or new items only (Shannon & Buckner, 2004) suggesting that activation is not likely due to the planning or implementation of a motor response.…”
mentioning
confidence: 99%